A path-dependent level set topology optimization with fracture criterion. (June 2021) - Wu, Chi; Fang, Jianguang; Zhou, Shiwei; Zhang, Zhongpu; Sun, Guangyong; Steven, Grant P.; Li, Qing
Highlights: A nonlinear topology optimization enhances fracture resistance of structures. Clear topological boundaries are guaranteed by a level-set approach. A p-norm phase-field constraint controls risks of fracture failure. Path dependent shape derivatives improve the accuracy of design sensitivity. 2D benchmark examples and a 3D real dental implant design are illustrated. Abstract: In this paper, a recently-developed phase-field damage model is incorporated into the topology optimization framework to take into account crack initiation and propagation in a path-dependent fashion. The proposed topological design can enhance fracture resistance of structures made of brittle materials such as advanced ceramics. For the first time, a path-dependent shape derivative is developed in a step-wise manner during the nonlinear fracture analysis, which enables to drive the topology optimization properly. To measure the fracture resistance of structure, a p -norm function is formulated to aggregate the phase-field variables into a single constraint. To demonstrate the effectiveness of the presented topology optimization procedure, three 2D benchmark examples with single-phasic material and one 3D biomedical example with biphasic materials are studied here. The comparison with the topological designs based upon conventional linear elastic finite element analysis without the damage model indicates that the proposed method can significantly improve the fracture resistance of structures with more efficient use of materials. The proposed method is anticipated to provide an effective approach for sophisticated path-dependent topological design of structures reducing severe stress concentration and high risks of fracture failure.